Evidence of MAOA genotype involvement in spatial ability in males - Mueller, Sven C. (Behav Brain Res, 2014)
Although the Monoamine Oxidase-A (MAOA) gene has been linked to spatial learning and memory in animal models, convincing evidence in humans is lacking. Performance on an ecologically-valid, virtual computer-based equivalent of the Morris Water Maze task was compared between 28 healthy males with the low MAOA transcriptional activity and 41 healthy age- and IQ-matched males with the high MAOA transcriptional activity. The results revealed consistently better performance (reduced heading error, shorter path length, and reduced failed trials) for the high MAOA activity individuals relative to the low activity individuals. By comparison, groups did not differ on pre-task variables or strategic measures such as first-move latency. The results provide novel evidence of MAOA gene involvement in human spatial navigation using a virtual analogue of the Morris Water Maze task.